Clauson–Kaas pyrrole synthesis using diverse catalysts: a transition from conventional to greener approach - Singh, Dileep Kumar; Kumar, Rajesh (Beilstein Journal of Organic Chemistry, 2023)
Pyrrole is an important aromatic heterocyclic scaffold found in many natural products and predominantly used in pharmaceuticals. Continuous efforts are being made to design and synthesize various pyrrole derivatives using different synthetic procedures. Among them, the Clauson–Kaas reaction is a very old and well-known method for synthesizing a large number of N-substituted pyrroles. In recent years, due to global warming and environmental concern, research laboratories and pharmaceutical industries around the world are searching for more environmentally friendly reaction conditions for synthesizing compounds. As a result, this review describes the use of various eco-friendly greener protocols to synthesize N-substituted pyrroles. This synthesis involves the reaction of various aliphatic/aromatic primary amines, and sulfonyl primary amines with 2,5-dimethoxytetrahydrofuran in the presence of numerous acid catalysts and transition metal catalysts. The goal of this review is to summarize the synthesis of various N-substituted pyrrole derivatives using a modified Clauson–Kaas reaction under diverse conventional and greener reaction conditions.
Keywords: catalyst; Clauson–Kaas pyrrole synthesis; 2,5-dimethoxytetrahydrofuran; green synthesis; microwave-assisted reaction; N-substituted pyrrole